FABRICATION OF NANOSTRUCTURED IRON AND ZINC PARTICLES BY DIOSPYROS CHLOROXYLON (ROXB.) LEAF EXTRACT: CHARACTERIZATION, ADSORPTION MODELING AND CARCINOGENIC DYE ADSORPTION APPLICATIONS - RAO, CHANDANA NARASIMHA; SUJATHA, M. (International Journal of Applied Pharmaceutics, 2024)
Objective: The discharge of these synthetic food dyes, such as sunset yellow and tartrazine, into industrial wastewater can lead to significant environmental and health issues. Its removal through effective adsorption presents an economical and efficient solution. Hence this study proposed to fabricate metal nanoparticles for the adsorption of carcinogenic dyes. Methods: The fabrication of iron and zinc nanoparticles employed the green synthesis methodology, utilizing an aqueous extract of Diospyros chloroxylon (Roxb.) as a reducing agent. The fabricated nanoparticles were characterized using TEM (Transmission Electron Microscopy), EDX (Energy-Dispersive X-ray Spectroscopy), SEM (Scanning Electron Microscopy), FTIR (Fourier-Transform Infrared Spectroscopy), and UV-Visible Spectroscopy. The nanoparticles were studied for its efficiency for the adsorption of carcinogenic dyes such as tartrazine and Sunset Yellow. Results: The iron nanoparticles were noticed to be uniformly distributed rod-shaped particles having smooth surfaces with 23-51 nm size range and an average particle size of 34 nm. Whereas the iron nanoparticles were noticed to be uniformly distributed spherical to oval shape with 35 nm to 68 nm size range and an average particle size 53 nm. The XRD results confirm that the iron nanoparticles were rhombohedral phase structure with 71.91 % of elemental iron whereas the zinc nanoparticles were noticed to be hexagonal Wurtzite phase structure having 69.4 % of metallic zinc. These synthesized nanoparticles were applied for the removal of sunset yellow and tartrazine dyes were investigated and found more than 90 % was removed. Adsorption isotherm study was best fitted with Langmuir model, and the maximal adsorption capacity was found to be 52.18 and 75.04 mg/g for sunset yellow using iron and zinc nanoparticles, whereas tartrazine maximum adsorption capacity was noticed to be 69.96 and 84.24 mg/g for iron and zinc nanoparticles. The adsorption reaction follows pseudo-first-order kinetics with high correlation coefficient. Repeated cycles of regeneration, reuse and stability showed very high removal efficiency and stability. Conclusion: The biosynthesis of metal nanoparticles demonstrates substantial promise for applications in environmental protection.